1986
DOI: 10.1002/eji.1830160204
|View full text |Cite
|
Sign up to set email alerts
|

Avian B cell precursors: Surface immunoglobulin expression is an early, possibly bursa‐independent event

Abstract: The avian bursa of Fabricius contains about 1 X 10(4) discrete follicles, each of which is colonized by a small number of lymphoid progenitor cells during embryonic life. We have previously shown (J.R.L. Pink et al., Eur. J. Immunol. 1985. 15:617) that all, or almost all B cell progenitors in the bursae of 4-day-old chicks express cell surface IgM. In this report, we have analyzed the distribution of cell surface (s)IgM-1 allotypes within individual follicles of (M-1a/M-1b) allotype heterozygous birds. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
46
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 29 publications
(4 reference statements)
8
46
0
Order By: Relevance
“…However, the frequency of bursal follicles that uniquely contained ϩ L Ϫ precursors was typically about 2%, indicating that the majority of ϩ L Ϫ bursal cells develop in follicles containing both ϩ L ϩ and ϩ L Ϫ cells. This is consistent with several reports demonstrating that a limited number of B cell precursors (between two and five) productively colonize each bursal follicle during embryogenesis and that there is no interfollicular trafficking of lymphoid cells within the bursa (10,21,22). Indeed in the case of a bursa containing 25% ϩ L Ϫ cells, in which each bursal follicle is colonized by three precursors, one would expect about 1.5% of follicles to have been colonized by three ϩ L Ϫ precursors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the frequency of bursal follicles that uniquely contained ϩ L Ϫ precursors was typically about 2%, indicating that the majority of ϩ L Ϫ bursal cells develop in follicles containing both ϩ L ϩ and ϩ L Ϫ cells. This is consistent with several reports demonstrating that a limited number of B cell precursors (between two and five) productively colonize each bursal follicle during embryogenesis and that there is no interfollicular trafficking of lymphoid cells within the bursa (10,21,22). Indeed in the case of a bursa containing 25% ϩ L Ϫ cells, in which each bursal follicle is colonized by three precursors, one would expect about 1.5% of follicles to have been colonized by three ϩ L Ϫ precursors.…”
Section: Discussionsupporting
confidence: 92%
“…Several experimental approaches have demonstrated that the B cells in each follicle are derived from a limited number (two to five) of sIg ϩ precursors and, further, that there is no traffic of B-lineage cells from one follicle to another (10,20,21). As a consequence, the increase in bursal cellularity observed after about embryonic day 15, when most immigration of B cell precursors to the bursa has ended, represents the consequences of B cell division within the bursa.…”
Section: Perinatal Deletion Of B Cells Expressing Surface Ig Moleculementioning
confidence: 99%
“…34). The bursa is composed of about 10 4 follicles, each of which is colonized by a few B cell precursors expressing surface immunoglobulin (Ig) M at 8 -14 embryonic day (35)(36)(37)(38). The precursors proliferate enormously, and their numbers finally reach to 2-5 ϫ 10 5 /follicle.…”
Section: Cd8mentioning
confidence: 99%
“…The bursa is colonized by a single wave of B cell precursors during embryogenesis starting at about embryonic day 8 (E8) and lasting about a week (11). Within the bursa, B cell precursors first are observed in the mesenchymal tissue, and 20,000-40,000 precursors subsequently migrate across the bursal epithelial basement membrane and begin to proliferate in oligoclonal clusters or epithelial buds from which the discrete follicles of the mature bursa are derived (12,13).…”
mentioning
confidence: 99%
“…Although Ig gene rearrangement is not intrinsically biased toward productive rearrangement, only those B cells that have undergone productive rearrangement are selected within the bursa (15). Because there is no detectable clonal expansion of B cell precursors in bursal follicles before the expression of sIg (13), transit across the basement membrane and subsequent precursor expansion in epithelial buds require sIg expression and represent a critical checkpoint in B lymphopoiesis.…”
mentioning
confidence: 99%